Analysis of Factors Affecting Tobacco Export Volumes di Central Java Province Year 2010-2021 - Nurcahyani, Weni; Sharma, Abhishek (Yayasan Sinergi Kawula Muda, 2023)
This study discusses the price of tobacco and tobacco production on the volume of tobacco exports in Central Java Province in 2010-2021. This study aims to determine the effect of tobacco prices and tobacco production on the volume of tobacco exports in Central Java Province in 2010-2021. This research is aquantitative research with the subject of this research is Central Java Province. The data used comes from the Central Java Province Statistics Center in 2010-2021. The data analysis method used is a multiple linear regression analysis model using the EViews 12 program. The results of this study indicate that there is a positive and significant effect of tobacco production on the volume of tobacco exports in Central Java Province, and there is a negative and insignificant effect of tobacco prices on export volumes. tobacco in Central Java Province. And there is a positive and significant effect of price and production on the volume of tobacco exports in Central Java Province.